Note: Position dependence of time signals picked off a microchannel plate detector - Ablikim, U.; Zohrabi, M.; Jochim, Bethany; Berry, B.; Severt, T.; Carnes, K. D.; Ben-Itzhak, I. (My University, 2015)
Using an ultrafast laser and a precision mask, we demonstrate that time signals picked off directly from a microchannel plate detector depend on the position of the hit. This causes a time spread of about 280 ps, which can affect the quality of imaging measurements using large detectors.